2009
DOI: 10.1111/j.1574-6968.2008.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinorhizobium meliloti rpoE2is necessary for H2O2stress resistance during the stationary growth phase

Abstract: RpoE2 is an extracytoplasmic sigma factor produced by Sinorhizobium meliloti during stationary growth phase. Its inactivation affected the synthesis of the superoxide dismutase, SodC, and catalase, KatC. The absence of SodC within the cell did not result in an increased sensitivity to extracellular superoxides. In contrast, the absence of KatC affected the resistance of S. meliloti to H(2)O(2) during the stationary growth phase. A katC strain behaved as an rpoE2 strain during an H(2)O(2) challenge, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…2); these results were in accordance with previous observations (Flechard et al, 2009;Sauviac et al, 2007). When cells were inoculated into 0.5 M NaCl GAS medium, b-glucuronidase activity increased immediately from 5±1 mmol min 21 (mg protein)…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…2); these results were in accordance with previous observations (Flechard et al, 2009;Sauviac et al, 2007). When cells were inoculated into 0.5 M NaCl GAS medium, b-glucuronidase activity increased immediately from 5±1 mmol min 21 (mg protein)…”
Section: Resultssupporting
confidence: 81%
“…The regulation of rpoE2 was analysed in the R635 strain carrying a wild-type copy of rpoE2 and a rpoE2-uidA fusion in the chromosome (Flechard et al, 2009 (Fig. 2); these results were in accordance with previous observations (Flechard et al, 2009;Sauviac et al, 2007).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Accordingly, we have shown that one of these sigma factors, RpoE2, is activated under various conditions, including heat shock, salt stress, and entry into stationary phase following nitrogen or carbon starvation (33), and is probably activated in planta as well (3; unpublished data). RpoE2 controls the transcription of a large regulon comprising at least 45 target genes, some of which encode stress-related functions, like katC, rpoH2, and sodC (10,33). S. meliloti rpoE2 mutants were recently described as more sensitive than the wild-type strain to desiccation (23) as well as to high H 2 O 2 concentrations in stationary phase (10), confirming the involvement of RpoE2 in stress responses.…”
mentioning
confidence: 88%
“…RpoE2 controls the transcription of a large regulon comprising at least 45 target genes, some of which encode stress-related functions, like katC, rpoH2, and sodC (10,33). S. meliloti rpoE2 mutants were recently described as more sensitive than the wild-type strain to desiccation (23) as well as to high H 2 O 2 concentrations in stationary phase (10), confirming the involvement of RpoE2 in stress responses. Interestingly, this sigma factor is largely conserved among alphaproteobacteria (33), and RpoE2 orthologues have been involved in stress resistance and/or host colonization in several species, including Brucella melitensis (7), Caulobacter crescentus (1), and more recently Rhizobium etli (28) and Bradyrhizobium japonicum (17).…”
mentioning
confidence: 88%